Send-a-Klaus - Olivera, Ana Bien Sofia R. (2013)
This film is about the Secret Santa Society: a group of devoted Christmas enthusiasts from all over the world conspiring with the elves that live in the North Pole. Since Santa Claus has already died, the Secret Santa Society has brought it upon itself to revive and perpetuate the world's belief in Santa Claus. It has been starting gift-giving missions worldwide, following and simulating Santa's method. In this film, three new accomplices of the society are chosen to be sent on a test mission to the Philippines, which poses challenges on their procedures, on account of it being a different environment. The film deconstructs a child's role in creating traditions and ways of celebrating for a holiday that has been institutionalized and perpetualized by powers greater and older than him. This thesis paper questions and challenges the age-old Santa Claus tradition and explores its origins in order to deconstruct the perceived necessity for it and to examine its place in a truly equal relationship between adults and children in our world. It explores the origins of Christmas, its evolving nature and current state represented in media, and the involvement of power in communicating these concepts, and influencing belief, from both the holders of power in media to their audiences, and from adults to children. Using concepts taken from Piagel's stages of cognitive development and existentialist philosophy, this thesis analyses the current status of this yearly phenomenon, and conceptualizes a better treatment and understanding of children and tradition of this particular time of year."